Nilai-Nilai Filosofis Simbol Galuh Kembang Cakra Rahayu Kancana - Yunie Astrianie; Yeni Wijayanti; Egi Nurholis (Jurnal Artefak, 2023)
The Cakra Rahayu Kancana symbol is an identity for the Galuh community in Ciamis Regency with philosophical values. The purpose of this research is to find out about the history and philosophical values of the Galuh Kembang Cakra Rahayu Kancana symbol. The method used in this research is a historical method with heuristic, criticism (external and internal), interpretation, and historiography stages. The results showed that the history of the rahayu kancana symbol stems from the legacy of Maharaja Prabu Niskala Wastu Kancana (1371-1475 AD) and the heritage of R.A.A Koesoemadiningrat (1839-1886 AD) during the Sunda-Galuh kingdom. The Galuh Cakra Rahayu Kancana symbol (Kembang Chakra) is found on the Astana Gede Kawali Site in inscriptions I and VI, while in the legacy of R.A.A Koesoemadiningrat, the Chakra is found on a trident or three-pointed spear at the Galuh Pakuan Museum. The philosophical value in the Cakra Rahayu Kancana symbol is about the spirit of leadership values conveyed by previous kings in the Sundanese-Galuh Tatars that the leadership that must be implemented is not only in the form of laws but must be carried out. going out well according to Tritangtu (tekad, ucap jeung lampah) must be aligned and balanced.